If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -9 = 7x + -3 Reorder the terms: -9 + 8x = 7x + -3 Reorder the terms: -9 + 8x = -3 + 7x Solving -9 + 8x = -3 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -9 + 8x + -7x = -3 + 7x + -7x Combine like terms: 8x + -7x = 1x -9 + 1x = -3 + 7x + -7x Combine like terms: 7x + -7x = 0 -9 + 1x = -3 + 0 -9 + 1x = -3 Add '9' to each side of the equation. -9 + 9 + 1x = -3 + 9 Combine like terms: -9 + 9 = 0 0 + 1x = -3 + 9 1x = -3 + 9 Combine like terms: -3 + 9 = 6 1x = 6 Divide each side by '1'. x = 6 Simplifying x = 6
| 9.4m= | | 0.5(3x+2)-0.2(x+6)=5 | | 0.33(2x+3)-0.2(x+6)=4 | | 3(n-9)=30 | | 12(x+3)=3(4x+5)+21 | | 3x^4=16x^2+12 | | 0.5(x+2)=0.25(2x+4) | | 0.2(4x+7)=3(4-4x)+15 | | 14m-2=2(8m-5) | | -5x+4= | | 21x=9x^4+6x^2+1 | | -0.16(x-18)+3(x+3)=x-6 | | 400=21x | | 9x+4=2(4x-2)+8 | | 3x^2=52x | | 4m^2n+5m^2p-4mnp= | | -3+9(x-1)=16x+4-7x | | 30x+25+-3x-3=30x-15 | | 6v-9=3(v-6) | | 9(u-6)=-7u-22 | | 7w-48=-3(w-4) | | 3x-8y=-18 | | 4(u+3)=-5u-33 | | (4x+3)(5x-6)= | | 3c+2=7c-3 | | 0.2(3x+5)-0.3(x+7)=4 | | 6x^2-29x+42=0 | | 0,4x=28 | | 10x+30=6x-4+-25x+-5 | | 3(5x+6)-0.5(x+5)=3 | | 10x+30=6x-4+-25+-5 | | -4(3p+4)-23=3(5p+5) |